2013
DOI: 10.1177/0954410012469493
|View full text |Cite
|
Sign up to set email alerts
|

European Space Agency intermediate experimental vehicle: Development of an independent aerothermodynamic database tool

Abstract: In the frame of the European Space Agency (ESA) Intermediate eXperimental Vehicle (IXV) project, ESA is coordinating a series of technical assistance activities aimed at verifying and supporting the IXV industrial design and development process. The technical assistance is operated by the Italian Space Agency, by means of the technical support of the Italian Aerospace Research Centre. One of the purposes of the activity is to develop an independent capability for the assessment and verification of the industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This real-life study case is the European Space Agency (ESA) IXV re-entry vehicle (shown in Fig. 1); more information about the IXV vehicle and the related ESA mission can be found in [14], [15] and references therein.…”
mentioning
confidence: 99%
“…This real-life study case is the European Space Agency (ESA) IXV re-entry vehicle (shown in Fig. 1); more information about the IXV vehicle and the related ESA mission can be found in [14], [15] and references therein.…”
mentioning
confidence: 99%